1995
DOI: 10.2307/3432508
|View full text |Cite
|
Sign up to set email alerts
|

The Goldfish as a Model for Studying Neuroestrogen Synthesis, Localization, and Action in the Brain and Visual System

Abstract: Organizational and activational effects of estrogen (E) in the central nervous system (CNS) are exerted directly by circulating E and indirectly after aromatization of circulating androgen to E in the brain itself. Understanding an environmental chemical's ability to disrupt E-dependent neural processes, therefore, requires attention to both pathways. Because aromatase (Aro) is highly expressed in teleost brain, when compared to mammals and other vertebrates, fish are technically advantageous for localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Teleost fishes are known to exhibit a high brain aromatase activity mainly due to the expression of cyp19a1b gene that encodes aromatase B (Callard et al 1995;Pellegrini et al 2005;Forlano et al 2006;Kah et al 2009). Recent studies based on both in situ hybridization and immunohistochemistry have demonstrated that the enzyme is restricted to radial glial cells and mostly abundant in the forebrain such as olfactory bulb, telencephalon, preoptic area, mediobasal hypothalamus, and pituitary (proximal pars distalis and neurohypophysis) (Robel and Baulieu 1994;Kah et al 2009;Halm et al 2003;Sakamoto et al 2001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Teleost fishes are known to exhibit a high brain aromatase activity mainly due to the expression of cyp19a1b gene that encodes aromatase B (Callard et al 1995;Pellegrini et al 2005;Forlano et al 2006;Kah et al 2009). Recent studies based on both in situ hybridization and immunohistochemistry have demonstrated that the enzyme is restricted to radial glial cells and mostly abundant in the forebrain such as olfactory bulb, telencephalon, preoptic area, mediobasal hypothalamus, and pituitary (proximal pars distalis and neurohypophysis) (Robel and Baulieu 1994;Kah et al 2009;Halm et al 2003;Sakamoto et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Fish brain has an exceptionally high level of aromatase activity; for example, 1,300 versus 1-5 fmol/mg protein/h in the hypothalamic/preoptic area of goldfish versus rat, mouse, rabbit, or hamster, respectively (Callard and Pasmanik 1987). Callard et al (1995) reported goldfish brain as a source of neuroestrogen and other steroids. Recently, it has been demonstrated that pregnenolone (P 5 ) and 17a-hydroxypregnenolone (17a-OH-P 5 ) were identified as cholesterol metabolites in the brain and pituitary gland of lacustrine sockeye salmon (Onchorhynchus nerka) during sexual maturation (Matsumoto et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…2). Gaining a better understanding of the regulation of E2 synthesis is reliant on studies on extragonadal metabolism of androgens and estrogens, and molecular characterization of multiple forms of 17␤-HSD in fish, although such reports [31,44,[49][50][51][52] have been restricted to date.…”
Section: E2mentioning
confidence: 99%
“…Bjerselius et al (2001) showed that a relatively brief exposure to estradiol (24-28 d) negatively impacted a number of courtship parameters in treated male goldfish paired with an unexposed, artificially-induced spawning female.Therefore, for males in particular, but also potentially for females, decreased fertility may be due to effects of treatment with estrogenic substances on reproductive behavior. Although certain data indicate that exogenous estrogen may impact brain p450arom activity, a causal link between altered p450aromatase activity and behavior have not been established (Callard et al, 1995;Melo and Ramsdell, 2001).…”
Section: Discussionmentioning
confidence: 97%